Development Of New Analytical Methods For Steroid Profiling For Doping Purposes - Manaf, Normaliza Abdul (2018)
The steroid profile compounds namely testosterone (T), epitestosterone (E), androsterone (A), etiocholanolone (Etio), 5alpha-androstane-3alpha,17beta-diol (5αAdiol), 5beta-androstane-3alpha,17beta-diol (5βAdiol) and the ratio of T to E (T/E)) has been determined in urine of male volunteers who consumed Tongkat Ali (TA) supplement using the solid phase extraction (SPE) and liquid-liquid extraction (LLE) method. From 47 samples, 11 samples violated the World Anti-Doping Agency (WADA) guidelines and confirmation by gas chromatography combustion isotope ratio mass spectrometry (GC-C-IRMS) showed 5 samples were consistent with the exogenous origin (Δδ13C > 3‰). Two microextraction methods, i.e., vortexassisted liquid-liquid microextraction (VALLME) and micro-solid phase extraction (μ-SPE) followed by LC-MS/MS were developed. Hypersil Gold C18 column (50 mm × 2.1 mm, 1.9 μm) with gradient elution resulted in baseline separation for compounds in about 8 min.